The Impact of Non-Wage Benefits on Job Quality and Labor Market Outcomes in the Developing World : What Do We Know? - Helppie, Brooke (World Bank, Washington, DC, 2012)
One indicator of job quality in the developing world is the extent to which workers are covered by nonwage mandated benefits. Mandated benefits are a class of labor market regulation that requires employers to provide their workers with some form of non-wage pay or benefits. These benefits are typically fully financed by the employer or the employer-worker pair, and administered at the firm level. This note summarizes the existing knowledge and research on the effects of providing higher mandated benefits on labor market outcomes. In particular, the authors focus on the evidence available for developing economies. The authors discuss the potential advantages and drawbacks of providing mandated benefits (as implied by economic theory), summarize some of the existing empirical literature on the impact of mandated benefits. This note sets out to introduce some of the theory and existing literature about mandated benefits, and to draw attention to the need for more research about the impact of this type of policy.